Analisis Serapan Kredit Investasi UMKM di Aceh - Hamdani Hamdani; Josi Farmiati (Jurnal EMT KITA, 2021)
This study aims to see the relationship between investment credit variables and the financial performance of MSMEs in the absorption of investment credit in Aceh. This study uses the 2019-2020 time series data by determining as many as 24 selected observers. The analytical method used in this study is a causality test with the help of Eviews 7 software. The study was conducted in Aceh Province in the period April-July 2020. The results showed that there was a one-way causality relationship between the Investment Credit (LKI) variable and the Financial Performance (LKK) variable. SMEs with a probability of 0.065 and a significance level of 10 percent. This means that investment loans that are channeled by banks to MSMEs can affect the financial performance of MSMEs and have a positive and significant relationship at the level of 10 percent. The results of the study indicate that the distribution of investment credit by banks to MSMEs in Aceh can have a positive impact on the financial growth of MSME businesses.